2021
DOI: 10.3389/fphar.2021.542891
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PhysicoChemical Parameters for Production of Cytotoxic Secondary Metabolites and Apoptosis Induction Activities in the Culture Extract of a Marine Algal–Derived Endophytic Fungus Aspergillus sp.

Abstract: The endophytic fungal community in the marine ecosystem has been demonstrated to be relevant source of novel and pharmacologically active secondary metabolites. The current study focused on the evaluation of cytotoxic and apoptosis induction potential in the culture extracts of endophytic fungi associated with Sargassum muticum, a marine brown alga. The cytotoxicity of the four marine endophytes, Aspergillus sp., Nigrospora sphaerica, Talaromyces purpureogenus, and Talaromyces stipitatus, was evaluated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…Previous studies have also demonstrated similar findings using marine algal-derived endophytic fungus Aspergillus sp. and apoptotic events in HeLa cells after treatment with fungal extract was evidenced using Annexin V-FITC/PI staining . A study performed using Annexin V-FITC and PI dual staining also showed that the fungal endophyte Cladosporium cladosporioides derived bioactive compound cladosporol A significantly induces apoptosis in MCF-7 cells …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have also demonstrated similar findings using marine algal-derived endophytic fungus Aspergillus sp. and apoptotic events in HeLa cells after treatment with fungal extract was evidenced using Annexin V-FITC/PI staining . A study performed using Annexin V-FITC and PI dual staining also showed that the fungal endophyte Cladosporium cladosporioides derived bioactive compound cladosporol A significantly induces apoptosis in MCF-7 cells …”
Section: Resultsmentioning
confidence: 97%
“…and apoptotic events in HeLa cells after treatment with fungal extract was evidenced using Annexin V-FITC/PI staining. 57 A study performed using Annexin V-FITC and PI dual staining also showed that the fungal endophyte Cladosporium cladosporioides derived bioactive compound cladosporol A significantly induces apoptosis in MCF-7 cells. 55 EA Extract of C. gloeosporioides Induces ROS Production and Depolarizes the Mitochondrial Membrane Potential in Breast Cancer Cells.…”
Section: Acsmentioning
confidence: 98%
“…The commercialization of secondary metabolites and VOCs derived from endophytes faces hurdles in sustainable release and economic upscale production. Media optimization, selection of potent microbial strains, and metabolic engineering are some of the parameters that can be employed (Sah et al, 2020;Kamat et al, 2020;Taritla et al, 2021) for the sustained production of desired antimicrobial secondary metabolites from endophytes. The addition of some of the precursors from the host system has also been studied during media optimization for continuous upscale production of the antimicrobial metabolites from endophytes during the fermentation process.…”
Section: Sustained Release and Cost-effective Production Of Microbial...mentioning
confidence: 99%
“…Thus, as an example, secondary metabolites obtained from Fusarium equiseti isolated from marine seaweed have shown activity against cancer cells [ 75 ]. Taritla et al [ 76 ] also reported compounds isolated from the extracts of the marine endophyte Aspergillus sp. that produced cytotoxicity and apoptosis in human cancer lines.…”
Section: Secondary Metabolites From Fungal Organismsmentioning
confidence: 99%